Impact of opioid substitution therapy on the HIV prevention benefit of antiretroviral therapy for people who inject drugs - Mukandavire, Christinah; Low, Andrea; Mburu, Gitau; Trickey, Adam; May, Margaret T; Davies, Charlotte F; French, Clare E; Looker, Katharine J; Rhodes, Tim; Platt, Lucy; Guise, Andy; Hickman, Matthew; et al. (AIDS (London), 2017)
A recent meta-analysis suggested that opioid substitution therapy (OST) increased uptake of antiretroviral treatment (ART) and HIV viral suppression. We modelled whether OST could improve the HIV prevention benefit achieved by ART among people who inject drugs (PWID). We modelled how introducing OST could improve the coverage of ART across a PWID population for different baseline ART coverage levels. Using existing data on how yearly HIV-transmission risk is related to HIV plasma viral load, changes in the level of viral suppression across the population were used to project the relative reduction in yearly HIV-transmission risk achieved by ART, with or without OST, compared with if there was no ART - defined here as the prevention effectiveness of ART. Owing to OST use increasing the chance of being on ART and achieving viral suppression if on ART, the prevention effectiveness of ART for PWID on OST (compared with PWID not on OST) increases by 44, 31, or 20% for a low (20%), moderate (40%), or high (60%) baseline ART coverage, respectively. Improvements in the population-level prevention effectiveness of ART are also achieved across all PWID, compared with if OST was not introduced. For instance, if OST is introduced at 40% coverage, the population-level prevention effectiveness of ART could increase by 27, 20, or 13% for a low (20%), moderate (40%), or high (60%) baseline ART coverage, respectively. OST could improve the HIV prevention benefit of ART; supporting strategies that aim to concurrently scale-up OST with ART.